ANALISIS FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN METODE PEMBAYARAN QRIS PADA MASYARAKAT MUSLIM DI DKI JAKARTA - Hilwa Syofa Kamila (2023)
In realizing safe and comfortable transactions and realizing digital changes in the financial sector, Bank Indonesia's target in implementing QRIS in Indonesia has set a target of 45 million users and 1 billion transaction volumes in 2023, but at this time the number of users has still not reached the target. The purpose of this research is to analyze the effect of maslahah, ease and risk on the intention to use the QRIS payment method among Muslim communities in DKI Jakarta. The research method used is quantitative data, with primary data collection by distributing questionnaires using a purposive sampling technique. Data analysis techniques in this study were tested using SEM PLS. This study used a sample of 180 respondents with the data analysis technique used was SEM PLS. The results of this study are that maslahah and convenience have a significant effect on intention to use while risk has no effect. It is hoped that this research can be input for QRIS service providers to improve existing conveniences and problems. The limitation of this study is that there are only three variables used in this study where there are still many other possible variables.